Predictors of VILI risk: driving pressure, 4DPRR and mechanical power ratio—an experimental study - Mauro Galizia; Valentina Ghidoni; Giulia Catozzi; Stefano Giovanazzi; Domenico Nocera; Beatrice Donati; Tommaso Pozzi; Rosanna D’Albo; Mattia Busana; Federica Romitti; Peter Herrmann; Onnen Moerer; et al. (Intensive Care Medicine Experimental)
Abstract Background Ventilator-induced lung injury (VILI) is one of the side effects of mechanical ventilation during ARDS; a prerequisite for averting it is the quantification of its risk factors associated with a given ventilatory setting. Many clinical variables have been proposed as predictors of VILI, of which driving pressure is the most widely used. In this study, we compared the performance of driving pressure, four times the driving pressure added to respiratory rate (4DPRR) and mechanical power ratio. Results In a study population of 121 previously healthy pigs exposed to harmful ventilation, we compared the association of driving pressure, 4DPRR and mechanical power ratio to lung weight, lung wet-to-dry and total histological score. All the three variables were associated with these outcomes. Driving pressure, 4DPRR and mechanical power ratio increase linearly with the lung weight (adjusted R 2 of 0.27, 0.36 and 0.40, respectively), the lung wet-to-dry ratio (adjusted R 2 of 0.19, 0.25 and 0.37) and the total histological score (adjusted R 2 of 0.26, 0.38 and 0.26). Using a multiple linear regression model with forward analysis, starting with tidal volume and progressively adding respiratory rate and positive end-expiratory pressure, and comparing the topic with the outcome variables, we obtained R2 values, respectively, of 0.07, 0.20, 0.42 for lung weight, 0.09, 0.19, 0.26 for lung wet-to-dry ratio and 0.07, 0.27, 0.43 for total histological score. Conclusions Driving pressure, 4DPRR and mechanical power ratio, were all associated with lung injury in healthy animals undergoing mechanical ventilation.